PMO-009 Are dietitians' recommendations for the post-discharge support of malnourished patients carried out in the community?. (28th May 2012) - Coleman, D; Baldwin, C; Weekes, C E
Abstract : Introduction: Disease-related malnutrition is common and is often identified during a hospital admission. Hospital stays tend to be short and therefore it is crucial that nutritional interventions begun in hospital are continued on discharge (Elia et al 2010). Research has highlighted failings in nutritional care across this boundary (van Bokhorst-de van der Schueren et al 2005; Bavelaar et al 2008). The aim of this study was to evaluate the continuation of dietetic interventions across the transition from acute to community care. Methods: All patients admitted to the acute medical wards and referred to a dietitian for nutrition support between 1 July and 30 September 2011 were considered eligible for this study. Patients were excluded if they died within 1-month of discharge, received enteral or parenteral nutrition, were receiving dietetic care for a long-term chronic condition or were still in hospital at 31 October 2011. Eligible patients or their carers were contacted to determine whether recommendations for their post-discharge oral nutritional support had been carried out. Data were analysed using SPSS V.17.0. Results: Of 108 patients, 27 (25 %) died before contact could be made and 17 (16 %) did not meet the inclusion criteria. 64 patients were included in this study of whom 35 (56%) were recommended one or more post-discharge dietetic interventions, including consumption of oral nutritional supplements and follow-up dietetic appointments. Of the 35 patients, it was not possible to contact 14 (40 %) within the time limits of the study. Contact was made with 21 patients of whom 17 (81%) received all the interventions recommended by the dietitian. Of the four patients who did not receive the recommended interventions, in 3 (75%) this was due to patient perception that treatment was no longer required. Of the 64 patients who met the inclusion criteria no comments were included in the discharge letter from the medical team on either nutritional status or dietetic input. Conclusion: In this study it was possible to contact only a small sample of eligible patients however, of those who were contacted the majority had received the post-discharge interventions recommended by the dietitian. Further studies are required to determine if dietetic recommendations are as likely to be carried out in patients who are more difficult to contact post discharge. Competing interests: None declared. References: 1. Bavelaar JW, Otter CD, van Bodegraven AA, et al. Clin Nutr 2008;27 :431–8. 2. Elia M, Russell CA, Stratton RJ. Proc Nutr Soc 2010;69 :470–6. 3. van Bokhorst-de van der Schueren MAE, Klinkenberg M, Thijs A. Eur J Clin Nutr 2005;59 :1129–35.